Key issues of digitization of archival documents: Kazakhstan and foreign experience (Journal of history, 2023)
The digital revolution affects not only all spheres of modern society, but also contributes to a radical change in their functions and meanings, from which archives have not remained aloof. In accordance with modern requirements for the availability of historical documents for researchers, their digitization is very relevant. Of course, the organization of this work, taking into account the national importance, uniqueness and preservation of the quality of archival documents, requires versatile technical support and appropriate qualifications of archive workers. Goals and objectives of the study. The purpose of the research work is to consider the best practices of foreign countries in this direction, ways to implement it, as well as assess the activities of the state in this process. In the course of writing this scientific study, the works of domestic and foreign scientists were widely used, affecting the problems of digitizing archival documents, as well as special state programs and regulatory legal acts. To achieve the goal of the research work, methods of systematization and comparison were applied. Results. As a result of the study, it was revealed that for the consistent and rapid digitization of archival documents, it is necessary to adopt a special program and develop appropriate methodological instructions at the state level. Conclusion. Currently, the current regulatory legal acts and the methodological base in the Republic of Kazakhstan are unsystematic and insufficient for the digitalization of archival documents. The results of scientific research can be used in the development of special state programs for the digitization of archival documents.